2017
DOI: 10.1002/cphc.201601323
|View full text |Cite
|
Sign up to set email alerts
|

Micelles versus Ribbons: How Congeners Drive the Self‐Assembly of Acidic Sophorolipid Biosurfactants

Abstract: Sophorolipids (SLs), a class of microbially derived biosurfactants, are reported by different research groups to have different self-assembled structures (either micelles or giant ribbons) under the same conditions. Here we explore the reasons behind these contradictory results and attribute these differences to the role of specific congeners that are present in minute quantities. We show that a sample composed of a majority of oleic acid (C18:1) sophorolipid in the presence of only 0.5 % (or more) of congener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Other congeners present include a mixture of sophorolipid structures with chain lengths of C 16 to C 18 containing 0 to 2 double bonds. The sophorolipids used in these studies are micelles forming, as recently described (23). Sophorolipid solutions of various concentrations (by mass) were prepared in the relevant culture media for in vitro experiments or sterile PBS for in vivo studies.…”
Section: Sophorolipidsmentioning
confidence: 99%
“…Other congeners present include a mixture of sophorolipid structures with chain lengths of C 16 to C 18 containing 0 to 2 double bonds. The sophorolipids used in these studies are micelles forming, as recently described (23). Sophorolipid solutions of various concentrations (by mass) were prepared in the relevant culture media for in vitro experiments or sterile PBS for in vivo studies.…”
Section: Sophorolipidsmentioning
confidence: 99%
“…55,58 We have recently shown that the micelle-ribbon duality depends on purity; a standard non-acetylated, monounsaturated, acidic sophorolipid batch forms micelles, unless it is contaminated with 15 wt% of the saturated congener, which induces the ribbon formation. 63 In terms of surface-adsorption properties of the sophorolipids, only alkyl ester derivatives have been explored, which nonetheless have shown adsorption on alumina being two orders of magnitude higher than on silica beyond a solution concentration of 10 À4 M. 64 The surface self-assembly and patterning ability of an aqueous micellar solution of non-acetylated, monounsaturated, acidic sophorolipids have been shown in the present investigation. We have investigated both the pH influence and the crucial role of the underlying surface (silica, gold, titanium dioxide-anatase structure).…”
Section: Introductionmentioning
confidence: 72%
“…55,58 However, this was not the case for the compound used in the present study, which only formed a stable micellar solution. In a recent study, 66 we have given the conditions for a micellar vs. fibrillar stability of sophorolipids in water at acidic pH. We were able to show that a standard batch of acidic non acetylated monounsaturated sophorolipid generally formed micelles in water, unless 15 wt% of the saturated form contaminated the batch.…”
Section: Effect Of Ph On Sophorolipid Surface Assemblymentioning
confidence: 89%
See 2 more Smart Citations